2017
DOI: 10.1177/0194599817703948
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Secondary Surgery after Modified Furlow Palatoplasty: A 20‐Year Single‐Surgeon Case Series

Abstract: Objective To determine the occurrence of velopharyngeal insufficiency (VPI) requiring surgery and fistula repair after primary palatoplasty using a "modified" Furlow technique. Study Design Case series with chart review. Setting Academic multidisciplinary cleft and craniofacial center. Subjects and Methods Children younger than 18 years at presentation, with unrepaired cleft palate, with or without cleft lip, including submucous clefts, who underwent palatoplasty were included. No cleft patients having primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 18 publications
(52 reference statements)
4
19
0
Order By: Relevance
“…This may imply that scaring from the initial palatoplasty and subsequent procedures does not affect maxillary growth restriction. Although many authors have focused on the relationship between surgical technique of the initial palatoplasty and maxillary growth [19][20][21][22][23], we believe technical nuances such as raising mucoperiosteal flaps or vomerine flaps may not alter the maxillary growth trajectory. Patient age at the time of repair also did not seem to have an effect either.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This may imply that scaring from the initial palatoplasty and subsequent procedures does not affect maxillary growth restriction. Although many authors have focused on the relationship between surgical technique of the initial palatoplasty and maxillary growth [19][20][21][22][23], we believe technical nuances such as raising mucoperiosteal flaps or vomerine flaps may not alter the maxillary growth trajectory. Patient age at the time of repair also did not seem to have an effect either.…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, a higher rate of secondary procedures has been reported after cleft palate closure in patients with ICP. As Chorney et al noted in their case series of 312 patients, patients with Veau type 2 have a statistically higher rate of pharyngeal flap requirement and oronasal fistula repair [21]. Similarly, in their study of 869 non-syndromic cleft palate patients, Jackson et al found that patients with ICP had the worst speech outcomes and higher rates of secondary surgery for velopharyngeal dysfunction [19].…”
Section: Discussionmentioning
confidence: 93%
“…The rate of VPI following primary palate repair requiring secondary surgery ranges from 5 to 29%. [44][45][46] There are a variety of factors that must be considered when reporting the incidence of VPI in cleft patients. First, there is currently no standardized assessment for diagnosing and rating the severity of VPI.…”
Section: Incidencementioning
confidence: 99%
“…2015; Lin et al, 2015;Moar et al, 2016;Yuan et al, 2016;Chorney et al, 2017;Li et al, 2017). Of the 6 articles that remained, 3 were excluded because of overlapping data with other articles.…”
Section: Inclusion Criteriamentioning
confidence: 99%